SharePoint Server 2010 administration 24-hour trainer - Reid, Martin; Crider, Bill.; Richardson, Clint; Safari eBooks ([S.l.] : Wrox, 2012)
"Covering all aspects of the SharePoint technology, this unique book-and-[video] combination provides expert guidance within each lesson in the book, which is then supplemented on the instructional [video]. The authors expose you to a variety of SharePoint Foundation 2010 topics, from organization concerns to training plans to programmer best practices, all aimed at helping you effortlessly find your way around SharePoint without a deep knowledge of the technology. You'll quickly learn to configure and administer a site or site collection using this book-and-[video] package."--Resource description page.
Title from title screen.
Author names and date of publication from resource description page (viewed Aug. 29, 2012).
Presenters, Bill Crider, Clint Richardson.
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Electronic books